2021
DOI: 10.1080/21655979.2021.1955578
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SOX21-AS1 modulates lung cancer progress upon microRNA miR-24-3p/PIM2 axis

Abstract: Lung cancer is a lethal cancer that threatens human health. Several studies have demonstrated the role of long non-coding RNAs (lncRNAs) in lung cancer. SOX21-AS1 is a newly discovered oncogenic lncRNA, but its molecular mechanism in lung cancer is not known. Here, the levels of SOX21-AS1, miR-24-3p, and PIM2 were examined in lung cancer and normal tissues. The relationships between miR-24-3p and SOX21-AS1 or PIM2 were predicted using bioinformatics tools and confirmed using a luciferase reporter assays. Colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Li et al demonstrated that SOX21-AS1 promotes cell proliferation, migration, and invasion in breast cancer (Li et al, 2021). The SOX21-AS1/miR-144-3p/PAK7 axis was shown to Frontiers in Pharmacology frontiersin.org be carcinogenic in glioma cells through the Wnt/β-catenin pathway (Gai and Yuan, 2020) and SOX21-AS1 was found upregulated in lung cancer (Wang et al, 2021). In CC, SOX21-AS1 showed hypomethylation (Du et al, 2021) and could promote CC progression (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al demonstrated that SOX21-AS1 promotes cell proliferation, migration, and invasion in breast cancer (Li et al, 2021). The SOX21-AS1/miR-144-3p/PAK7 axis was shown to Frontiers in Pharmacology frontiersin.org be carcinogenic in glioma cells through the Wnt/β-catenin pathway (Gai and Yuan, 2020) and SOX21-AS1 was found upregulated in lung cancer (Wang et al, 2021). In CC, SOX21-AS1 showed hypomethylation (Du et al, 2021) and could promote CC progression (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The p < 0.05 was ascertained to be statistically significant. All experiments were repeated three times [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, cells in the bottom chamber were dyed with crystal violet (Sangon). Cell numbers were counted by a microscope (Nikon, Japan) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%